B.p.r.d. omnibus, volume 9 ebook - Arcudi, John (B.P.R.D. (2002), 2024)
Hell on Earth comes to an end when the B.P.R.D. must defend Earth from one of the mythical Ogdru Jahad, the dragon believed to bring about the end of the world.The agents must destroy the dragon and the countless monsters it creates. Elsewhere, Russian occult director seeks help from a demon as he follows her through Hell.Collects B.P.R.D.: Hell on Earth: Nowhere, Nothing, Never; Modern Prometheus; End of Days; and Cometh the Hour.